Synthetic Biology and Its Envisioned Significance for Modern Medicine - Braun, Matthias; Ried, Jens; Dabrock, Peter (Handbook of the Philosophy of Medicine, 2015)
Synthetic Biology (SB) is one of the leading branches within the current bundle of emerging biotechnologies. Following the hypothesis that the further development of SB will be negotiated at the interface of science and society, this chapter points out the current developments and challenges within SB by addressing the scientific as well as the societal issues.